Colorism Self-Concept among Junior High School Students (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Colorism self-concept is one of the factors that can influence an individual way of thinking about themselves and others, shaping perceptions of beauty, worth, and social status based on skin tone. By studying high school students' views on colorism, researchers can understand how perceptions about skin tone describe their formation of attitude towards others, their association with peers, and self- esteem. This study aims to descrbe the colorism self-concept among the respondents. The researchers employed quantitative descriptive-correlational study to collect data from the 163 Junior High School students who are enrolled in Union Christian College through a survey questionnaire. The researchers used frequency count and percentage to present their profile, weighted mean for their colorism self-concept, and Pearson Product Moment Correlation for the relationship between the variables. The study revealed that the colorism self-concept is high meaning the colorism in this area is high while the result in Attraction is moderate. Furthermore, the result in Impression Formation, Affiliation, and Upward Mobility are low, indicating that the colorism in these areas are low. Also, colorism self- concept had a weak and negative relationship with sex while there was no correlation with grade level. Furthermore, female respondents who are part to any ethnic group are most likely experience colorism. The findings imply that there is a need to enhance how the students perceive colorism as a way to improve their association and attitude towards others, and improve their self-esteem regardless of their skin tone. It's crucial to address these findings by implementing interventions aimed at fostering inclusivity and combating colorism biases, particularly targeting female students across diverse ethnic groups, while considering the weak negative association with sex and the absence of correlation with grade level. The researchers recommend that programs promoting self-confidence and inclusivity be conducted to positively improve their colorism self-concept.
Keywords: colorism self-concept; self-confidence; inclusivity